(untitled) (The Pakistan Development Review, 1982)
Since the crop environment in Pakistan is still greatly influenced by the vagaries of Nature, it is important to separate this effect from The true process of crop growth. Attempts to capture the large random fluctuations from the trend line by using a single variable for weather arc not fruitful at all. In the absence of a composite index of weather, the indirect method used in this study allows identification of normal and abnormal years, which can then be used for forecasting or even insurance planning purposes.